2018
DOI: 10.2147/cmar.s172725
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of primary tumor surgery in minor salivary-gland carcinoma patients with distant metastases at diagnosis: first evidence from a SEER-based study

Abstract: PurposeThe prognostic value of primary tumor surgery (PTS) in minor salivary-gland carcinoma (MiSGC) with distant metastasis (DM) at diagnosis has never been investigated. In this study, we aimed to provide the first evidence.Patients and methodsThe Surveillance, Epidemiology, and End Results (SEER) database was employed to identify MiSGC patients with DM at diagnosis. The prognostic value of PTS was evaluated by Kaplan–Meier methods, log-rank analyses, and multivariate Cox proportional-hazard regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(35 reference statements)
1
11
1
Order By: Relevance
“…However, some other studies based on the SEER database have also reported this disadvantage. They confirmed that it was impossible that this unadjusted confounding factor alone contributed to the highly significant prognostic value of RP or BT in highly selected groups (23)(24)(25)(26)(27). Secondly, the SEER database only had information of five specific organs of metastases, which could not include all types of metastasis developed in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other studies based on the SEER database have also reported this disadvantage. They confirmed that it was impossible that this unadjusted confounding factor alone contributed to the highly significant prognostic value of RP or BT in highly selected groups (23)(24)(25)(26)(27). Secondly, the SEER database only had information of five specific organs of metastases, which could not include all types of metastasis developed in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…We explored the National Cancer Institute's SEER 9 regulations research data (November 2017 Sub; 1973–2015; Katrina/Rita Population Adjustment) to evaluate the risks of SPM in MiSGC patients who survived for ≥6 months after diagnosis. The inclusion criteria were as follows: (1) International Classification of Diseases for Oncology, third edition (ICD‐O‐3) histologic codes for adenocarcinoma (8140, 8147, 8290, 8310, 8410, 8440, 8480, 8525, 8550, and 8491), adenoid cystic carcinoma (8200), mucoepidermoid carcinoma (8430), mixed subtype (8980), or other rare carcinomas (8012, 8041, 8082, 8500, 8562, and 8982) 14 ; (2) ICD‐O‐3 primary sites code for oral cavity (C00.0–C00.9, C02.0–C02.3, C02.8–C02.9, C03.0–C03.9, C04.0–C04.9, C05.0, and C06.0–C06.1), nasopharynx (C11.0–C11.9), oropharynx (C01.9, C02.4, C05.1–C05.2, and C09.0–C10.9), larynx (C32.0–C32.9), hypopharynx (C12.9–C13.2), nasal cavity (C30.0), and paranasal sinus (C31.0–C31.9); the anatomic sites as well as pathological categories in our including criteria were mainly based on ICD‐O‐3 topographical and histological codes that were proposed or adopted by previous studies; 4,7,15‐17 (3) tumor with malignant behavior; and (4) tumor with histologic confirmation (+) 14 . To exclude synchronous cancers, we excluded any patients in whom the second primary was detected within 6 months of diagnosis of MiSGC, followed by the criteria modified by National Cancer Institute 18 and was consistent with previous standard approaches 12,19,20 .…”
Section: Methodsmentioning
confidence: 99%
“…Salivary gland (SG) neoplasms account for 3%–5% of all head and neck malignancies with a total estimated incidence of 0.9 per 100 000 in the United States 1,2 . Minor salivary gland cancers (MiSGCs) constitute approximately 20% of total SG malignancies 3,4 . The annual incidence of minor salivary gland malignancies has been estimated to be 0.16 to 0.4 per 100 000 persons in the UK Nottingham population 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Growing studies have demonstrated prolonged survival in metastatic diseases when aggressive local surgeries were carried out. [12][13][14][15] Venigalla et al found that patients with cervical cancer with disseminated disease would benefit from locally definitive treatment (concurrent chemotherapy or definitive surgery), and median overall survival (OS) time is elevated by 9.1 months. However, only 14% of patients in the definitive treatment group underwent definitive surgery, and the relative role of surgery on survival was not investigated.…”
Section: Introductionmentioning
confidence: 99%